Potential Application of Treated Bauxite Residue - Kumar S.; Verma A.K.; Prasad A. (My University, 2025)
Bauxite residue is a significant industrial solid waste residue produced by the Bayer process for the extraction of alumina from bauxite ores. It is usually disposed off in the form of slurry in the nearby areas of the alumina industry. About 400 million tons of bauxite residues are produced annually worldwide. However, it has some environmental and logistical problems in handling and disposal due to high alkalinity (pH 10–13.5), sodicity, fine particles, and some trace metal content. Thus, it cannot be used directly and requires pre-treatment before any civil engineering applications. In view of the given above, an attempt has been made to explore the potential of the bauxite residue for some civil engineering applications. The present study investigates the effect of various parameters on the strength and durability of bauxite residue. Further, a series of laboratory tests considering various parameters were carried out. The results indicate that treated bauxite residue with a certain combination of parameters (dry density, moisture content, and curing time) can be used as an unfired brick for low-cost housing. © 2021, Springer Nature Singapore Pte Ltd.